Nursing Professional Values Scale (NPVS-3) in an Austrian context: validation of a scale and reliability assessment - Nertila Podgorica; Chennyfer Dobbins Abi Rached; Nicole Yamada Crescente; Christoph Zenzmaier; Gerhard Müller (BMC, 2024)
Abstract Background The Nurses Professional Values Scale-3 (NPVS-3) is a psychometric instrument derived from a set of values initially established by the American Nurses Association (ANA) Code of Ethics. The present study evaluates the reliability of the NPVS-3 scale for nursing students and nurses in Austria. Methods A cross-sectional methodological study was conducted on 209 research participants, comprising 139 nursing students and 70 nurses, with the objective of determining the reliability of the Austrian version of the scale. A multilevel approach was employed in the study, encompassing cultural and linguistic validation, content validity, face validity, and construct validity. The scale translation was performed per the established translation stages of back-translation and was subsequently reviewed by an expert committee. The translated instrument was applied to the participants who completed an online survey between April and July 2023. Internal consistency was evaluated using Cronbach's alpha, while construct validity was assessed using confirmatory factor analysis (CFA). Results The Cronbach's alpha values obtained were deemed appropriate, with the following results: Caring (0.852), Activism (0.832), and Professionalism (0.676). Through factorial analysis, three factors were identified as original NPVS-3 and construct validity was verified. Conclusion The Austrian version of the NPVS-3 demonstrated satisfactory validity, efficiently evaluating the professional values of nurses and nursing students in Austria.